LISTENING IN THE WIDER CONTEXT - Scientific advisor: Teshaboyeva Nafisa Student of group 101-23: Husanova Ruxshona Rustam qizi (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
Listening, often regarded as a foundational skill in language acquisition, extends beyond mere comprehension to significant implications in broader contexts. This paper explores the multifaceted role of listening within educational, social, and professional settings. It highlights the importance of active listening and its impact on effective communication, collaboration, and interpersonal relationships. By examining various listening strategies and assessment methods, the study demonstrates how fostering strong listening skills can enhance overall language proficiency and contribute to cognitive development. Furthermore, it discusses challenges learners face in diverse environments and presents practical solutions for educators to support listening skill development. Ultimately, this work advocates for a comprehensive approach to listening that recognizes its value in facilitating engagement and understanding across various life contexts.